2012
DOI: 10.12681/mms.309
|View full text |Cite
|
Sign up to set email alerts
|

First record of Palaemon macrodactylus Rathbun, 1902 (Decapoda, Palaemonidae) in the western Mediterranean

Abstract: The Mediterranean Sea is one of the world’s hotspots for marine bio-invasions. Most invasions are first documented based on an initial record of occasional adult captures. However, reports of larval stages could indicate that there is an adult population that is reproducing and therefore well established in the area. The spread of the oriental shrimp, Palaemon macrodactylus, from its native estuarine waters of southeast Asia to new regions worldwide is well documented. We report the first record of this specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…As penaeids are quite sensitive to the WSSV, some concern may arise for the farming of Marsupenaeus japonicus, carried on since 1980's in some North Adriatic lagoons, and for the fishery of the autochthonous stock of Melicertus kerathurus. Ashelby et al (2013) suggested that the oriental shrimp will likely diffuse in the near future in north-eastern Europe (Baltic Sea), southern Norway, north-western Africa, and pointed out that invasion of the Mediterranean region might already have begun (based on the larval evidence reported by Torres et al, 2012). The present data fully confirm this prediction and we can expect to see this shrimp in other Mediterranean brackish habitats in the near future.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…As penaeids are quite sensitive to the WSSV, some concern may arise for the farming of Marsupenaeus japonicus, carried on since 1980's in some North Adriatic lagoons, and for the fishery of the autochthonous stock of Melicertus kerathurus. Ashelby et al (2013) suggested that the oriental shrimp will likely diffuse in the near future in north-eastern Europe (Baltic Sea), southern Norway, north-western Africa, and pointed out that invasion of the Mediterranean region might already have begun (based on the larval evidence reported by Torres et al, 2012). The present data fully confirm this prediction and we can expect to see this shrimp in other Mediterranean brackish habitats in the near future.…”
Section: Discussionsupporting
confidence: 81%
“…Ashelby et al (2013) suggested the possibility that these larvae might have been released by a passing vessel during offshore ballast water exchange, instead of originating from a nearby still undetected population as hypothesized by Torres et al (2012). Photographic evidence (no specimens could be collected at that time) of the presence of P. macrodactylus in the lagoon of Sacca di Goro (northern Adriatic Sea) was provided by Rinaldi (2012).…”
Section: Palaemon Macrodactylusmentioning
confidence: 99%
See 1 more Smart Citation
“…This could be due to the use of a 200-μm mesh net, which does not sample effectively individuals smaller than 450 μm (Hopcroft et al, 2001). Their absence from previous studies often happens when studies do not aim at detecting allochthonous species, and the presence of such species is not noted by non-specialized taxonomists; consequently, specimens of alien species are accidentally referred to as similar congeneric native species or their juveniles (Torres et al, 2012). It is unlikely that this species entered the Mediterranean Sea via the Strait of Gibraltar through natural expansion, because P. schmackeri is primarily distributed along the western coast of the Atlantic Ocean, and to the best of our knowledge has not yet been recorded along the eastern coast of this ocean close to the Gibraltar Strait.…”
Section: Discussionmentioning
confidence: 99%
“…Decapods are the prevalent group, followed by copepods. The latest records are the shrimp Palaemon macrodactylus (Torres et al, 2012) in the WMED, and two parasitic copepods, Caligus fugu and Taeniacanthus lagocephali, caught on a Lessepsian puffer fish in the EMED (Özak et al, 2012). We have added the unusual finding of the brine shrimp Artemia franciscana in the saltworks of Margherita di Savoia, Apulia (Mura et al, 2006 (Bianchi & Morri, 1996).…”
Section: A Updates In Species Recordsmentioning
confidence: 99%